ANALISIS REALISASI ANGGARAN UNTUK MENILAI EFEKTIVITAS KINERJA ANGGARAN PADA DINAS PERHUBUNGAN KABUPATEN TULUNGAGUNG - Marlena; Retno Murnisari; Nikita Larasati Purbaningrum (JAT : Journal Of Accounting and Tax, 2022)
AbstractThis study aims to analyze how the realization of the budget in assessing theeffectiveness of performance at the Department of Transportation of TulungagungRegency. The research method used is descriptive quantitative. The data collectionincludes data collection, observation, interviews and literature review. Researchvariables are Budget Realization and Budget Performance Effectiveness. The results ofthis study indicate that the Budget Realization Analysis to Assess the Effectiveness ofBudget Performance at the Tulungagung Regency Transportation Service for the 2019-2021 period is said to be very effective. Because the data that has been obtained byresearchers has been processed and get good results too AbstrakPenelitian ini bertujuan untuk menganalisis bagaimana realisasi anggarandalam menilai efektivitas kinerja pada Dinas Perhubungan KabupatenTulungagung. Metode penelitian yang digunakan adalah Deskriptif Kuantitatif.Pengumpulan datanya meliputi pengambilan data, observasi, wawancara dantinjauan pustaka. Variabel Penelitian adalah Realisasi Anggaran dan EfektivitasKinerja Anggaran. Hasil dari penelitian ini menunjukkan bahwa AnalisisRealisasi Anggaran Untuk Menilai Efektivitas Kinerja Anggaran pada DinasPerhubungan Kabupaten Tulungagung periode 2019-2021 dikatakan sangatefektif. Karena data-data yang telah peroleh peneliti sudah diolah danmendapatkan hasil yang baik pula.